Priapism in Patients with Chronic Myeloid Leukemia (CML): A Systematic Review : Priapism in Chronic Myeloid Leukemia - Ali, Elrazi; Soliman, Ashraf; De Sanctis, Vincenzo; Nussbaumer, Doris; Yassin, Mohamed (Acta Biomedica Atenei Parmensis, 2021)
Background: Priapism is defined as a penile erection that persists four or more hours and is unrelated to sexual stimulation. Priapism resulting from hematologic malignancy is most likely caused by venous obstruction from microemboli/thrombi and hyperviscosity caused by the increased number of circulating leukocytes in mature and immature forms. In patients with leukemia, 50% of cases of priapism are due to Chronic Myeloid Leukemia (CML). We present a systematic review of priapism in CML. Acquisition of evidence: An extensive literature research was carried out in PubMed, Google Scholar, SCOPUS, and Science Citation Index databases... The search included cases up to 4th August 2020. Synthesis of evidence: A total of 68 articles were found and included in our review, including 3 reviews from three different centers.  We found 68 articles (102 patients; figure 1) and several case reports on priapism in CML. Priapism was noticed in some patients at the first presentation of CML. However, it was infrequently reported during the start of treatment, following the stop of medication and post-splenectomy. The mean age at presentation was 27.4 years, and the mean time from onset of priapism to the time to get medical attention (presentation) was 78.2 hours. The mean white blood cell count associated with priapism was 321.29x109/L, and the mean platelet count was 569 x10 9/L. The chronic phase of CML was the most common phase where priapism occurred. Most patients were Asian (>50%). Nearly a quarter of patients (27.4%) developed permanent erectile dysfunction. Conclusions: Priapism is a urological emergency requiring urgent multidisciplinary management to prevent erectile dysfunction. Because of the relatively rare occurrence of priapism in CML patients, there is no standard treatment protocol.